Does gender affect the outcomes of patients in program of managed care for acute myocardial infarction - Katarzyna Wilkosz; Maciej Wybraniec; Marcin Wita; Joanna Fluder; Monika Malta; Jarosław Chmurawa; Andrzej Kubicjus; Krystian Wita (Medical Journals Sweden, 2021)
Background: There is increasing evidence that cardiac rehabilitation and regular follow-ups are associated with reduced mortality and morbidity. A programme of Managed Care for Patients with Acute Myocardial Infarction was developed in Poland (MC-AMI; in Polish, KOS-zawał), based on current scientific evidence. However, there is a lack of data on possible improvement in long-term prognosis among women after acute myocardial infarction. Aims: To compare the male and female population who participated in MC-AMI, regarding major cardiovascular events, defined as a composite of death, recurrent myocardial infarction, and hospital-ization for heart failure, in a 1-year follow-up. Methods: A prospective research study from a single cardiology care centre. The study compared 2 groups: women and men who agreed to participate in the MC-AMI programme. Results: A total of 529 patients were included in the study (167 women and 362 men). In the 12-month follow-up, the difference in major cardiovascular events events was not statistically significant for women and men, respectively (11.38% women vs 11.33% men; p = 0.98). Cox multivariate regression analysis of the surveyed population showed that coronary heart disease, diabetes mellitus type II, and previous percutaneous coronary intervention were significantly correlated with the primary endpoint. Conclusion: Women participating in the MC-AMI programme did not have a worse prognosis regarding major cardiovascular events, compared with men in a 12-month follow-up. Given the benefits of the MC-AMI programme, the proportion of women participating in the programme should be increased. Lay Abstract Despite the development of new treatment techniques, myocardial infarction remains one of the leading causes of death in Europe. Women account for 48% of patients with myocardial infarction. Due to clinical, economic, demographic and sociological conditions, the long-term prognosis for women after myocardial infarction is worse than for men. A national programme of managed care after myocardial infarction has been introduced in 2019 year in Poland (MC-AMI; in Polish, KOS-zawał). The programme comprises 4 stages: hospitalization and treatment of the acute phase of myocardial infarction; early cardiological rehabilitation; regular follow-up at in-patient clinic; and evaluation of indications for advanced methods of treatment of post-infarction complications. Implementation of this programme in Poland has result-ed in a comparable long-term prognosis being achieved for the male and female population. Widespread use of the MC-AMI programme is a promising option to equal-ize the prognosis for both sexes after a heart attack.